Does Active Service Intervention Drive More Complaints on Social Media? The Roles of Service Quality and Awareness. Issue 3 (3rd July 2021) - Sun, Shujing; Gao, Yang; Rui, Huaxia
ABSTRACT: Despite many advantages of social media as a customer service channel, there is a concern that active service intervention encourages excessive service complaints. Our paper casts doubt on this misconception by examining the dynamics between social media customer complaints and brand service interventions. We find service interventions indeed cause more complaints, yet this increase is driven by service awareness rather than chronic complaining. Due to the publicity and connectivity of social media, customers learn about the new service channel by observing customer service delivery to others—a mechanism that is unique to social media customer service and does not exist for traditional call centers. Importantly, high-quality service reduces future complaints. As a result, proactive customer service is a sound strategy on social media, as long as firms dedicate to service quality. Hence, firms should be less concerned about whether to respond and more focused on how to respond to customer complaints.